Will Product Portfolio Management profit from Cost Scaling Equations for Offshore Wind Turbine Components? – Qualitative Analysis – - Maximilian MEISSNER; Michal GREGUS (Communications of International Proceedings, 2021)
In this article we examine the research question “if offshore wind OEM´s Product Portfolio Management (PPM) will benefit from cost forecast equations for turbines main components within their portfolio decision process?” by an extensive literature review of product portfolio decisions within PPM in the wind industry. In addition, two key experts from a leading offshore wind turbine OEM have been interviewed to answer this question and the method of qualitative content analysis as outlined by Mayring has been used to analyze the interviews and interpret the findings. It was analyzed if offshore wind turbine OEM PPM agrees to the from the literature predicted turbine growth and what they see as the real risks and cost drivers correlating with it. In addition, it was evaluated if cost forecast equations could improve the CAPEX estimations in the portfolio decision process. Therefore, this paper provides the scientific foundation by presenting the key concerns of offshore wind turbine OEM´s PPM for the predicted growth and the improvements in product portfolio decision process through available cost forecast equations for main components. Aiming to use the presented results in future research in order to create accurate cost forecast models for the turbine main components and with it the creation of an overall turbine CAPEX scaling model.
Keywords: Portfolio Management; Portfolio Decision Making; Offshore Wind Turbines; Cost Scaling; Renewable Energy